GAMBARAN KOLABORASI DARING DI MASA PANDEMI COVID-19 BERBASIS TRA (Theory of Reasoned Action): STUDI KASUS UNIVERSITAS X - Jap Tji Beng; Alivia Fitriani Amanto; Desella Chandra; Mei Ie; Nina Perlita; Mirabella Mirabella; Sri Tiatri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The impact of the COVID-19 pandemic has caused a learning transition from offline to online. This study is part of a wider study, and aims to get an overview of online meetings in the context of education, in the late teens group.This research method is quantitative descriptive, with data collection using a questionnaire that is administered through the G-Form. The research participants were 139 late teens (48,2% male dan 51,8% female)who were college students X. The results of this study showed several findings: (a) the main way of communicating using a cellphone accompanied by security measures by activating a password; (b) participants hold the most online meetings with Zoom; (c) online database access, for example email data is required; (d) they store and sync online content to share real-time data files using google drive with storage capacities ranging from 1GB to 25GB; (e) participants are less likely to sync online calendars and do not require SharePoint and Microsoft Project software; (f) participants do not have problems regarding operational compatibility in carrying out online collaboration, they usually use laptops and need electricity as an energy source; (g) the most important factor of a good network provider is the internet provider, because of the problems commonly encountered when using online facilities related to documents, especially when editing in real-time and sharing large files; (h) participants perform the work of sharing notes, synchronizing documents across devices, and granting permission to share content with colleagues using services provided by Google such as GDocs; (i) participants do work with scheduling features, especially when creating calendars with colleagues using cloud calendar services (google/apple/teams). Through the TRA approach, by discovering the behaviors of using technology in this online collaboration, it can be concluded that in general, research participants have positive beliefs and evaluations of the technology used in online collaboration. The use of technology for online collaboration has also begun to become the accepted norm for the group of late teens who are college students. The findings of this study form the basis for further, broader studies of the described collaboration with Vygotsky's theories.